Integrated analysis of transcriptomics, proteomics and metabolomics data reveals the role of SLC39A1 in renal cell carcinoma - Yuan, Yulin; Liu, Zimeng; Li, Bohan; Gong, Zheng; Piao, Chiyuan; Du, Yang; Zhan, Bo; Zhang, Zhe; Dong, Xiao (Frontiers in Cell and Developmental Biology, 2022)
Purpose: Accumulating evidence suggests that solute carrier family 39 member 1 (SLC39A1) is a tumor suppressor, but the underlying mechanism in renal cell carcinoma (RCC) is poorly understood. Methods: OSRC-2 renal cancer cells were first transfected with SLC39A1 overexpressed vectors and empty vectors and then used in transcriptomics, proteomics, and metabolomics integrated analyses. Results: SLC39A1 significantly altered several metabolisms at transcriptional, protein and metabolic levels, including purine and pyrimidine metabolism, amino acids and derivatives metabolism, lactose metabolism, and free fatty acid metabolism. Additionally, SLC39A1 triggered significant crosstalk in PI3K-AKT signal pathway, cAMP signal pathway, and peroxisome proliferators-activated receptor (PPAR) signal pathway and promoted ferroptosis in renal cancer cells. Conclusion: We found that SLC39A1 transfection impaired tumor metabolism and perturbed tumor metabolism-related pathways to suppress cell proliferation, migration, and cell cycle progression in RCC cells. These multi-omics analyses results provided both a macroscopic picture of molecular perturbation by SLC39A1 and novel insights into RCC tumorigenesis and development.